Law No. 66 of the year 2016 On Amending Certain Provisions of the Law on the Central Bank, Banking Sector and Money Promulgated by Law No. 88 of the year 2003 = قانون رقم 66 لسنة 2016 بتعديل بعض أحكام قانون البنك المركزى والجهاز المصرفى والنقد الصادر بالقانون رقم 88 لسنة 2003 - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic